2003
DOI: 10.4319/lo.2003.48.4.1601
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal shift in net ecosystem production in a tropical estuary

Abstract: Net ecosystem production was examined in the Mandovi and Zuari estuaries (southwestern India) and the adjoining coastal waters for a period of 1 yr (January to December 1998). The study period encompassed premonsoon, monsoon, and postmonsoon seasons. At the estuarine stations, net ecosystem production showed monthly variation and a transition from net autotrophy of 49 mmol C m Ϫ2 d Ϫ1 during the nonmonsoon seasons (premonsoon and postmonsoon) to net heterotrophy of Ϫ46 mmol C m Ϫ2 d Ϫ1 in the monsoon season. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 36 publications
6
40
0
8
Order By: Relevance
“…the bacterial carbon demand is met either by the exogenous organic carbon or DOC reservoir source, in addition to those derived from local contemporaneous phytoplankton. This shift in the trophic status corroborates with our earlier findings using the alternative approach of net oxygen and CO 2 gas flux across air-sea interface in this estuarine system [40]. Significant relationship (p < 0.01) between BP and PP in the dry pre-monsoon season suggested PP to be the dominant source of carbon for bacterioplankton growth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…the bacterial carbon demand is met either by the exogenous organic carbon or DOC reservoir source, in addition to those derived from local contemporaneous phytoplankton. This shift in the trophic status corroborates with our earlier findings using the alternative approach of net oxygen and CO 2 gas flux across air-sea interface in this estuarine system [40]. Significant relationship (p < 0.01) between BP and PP in the dry pre-monsoon season suggested PP to be the dominant source of carbon for bacterioplankton growth.…”
Section: Discussionsupporting
confidence: 91%
“…BP and BR. A significant relationship between BGE and BP, (not BR) at the estuaries, as seen in the present study, has been reported previously [40,42]. Across a range of aquatic ecosystems, BP was consistently shown to be more variable than BR [eg.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Seasonal shifts from auto-to heterotrophy according to river flow variations have also been reported. For example, heterotrophy occurs during monsoon periods in tropical estuaries, when increased allochthonous organic input leads to enhanced respiration (Ram et al, 2003).…”
Section: Introductionmentioning
confidence: 99%